Knowledge, Attitudes and Practices Related to HIV Stigma and Discrimination Among Healthcare Workers in Oman - Samir Shah; Ali Elgalib; Adil Al-Wahaibi; Maha Al-Fori; Prasanna Raju; Mahmood Al-Skaiti; Huda N. Al-Mashani; Kishor Duthade; Iyad Omaar; Muhammad Muqeetullah; Nilanjan Mitra; Parag Shah; et al. (Sultan Qaboos University Medical Journal, 2020)
Objectives: Stigma and discrimination undermine the quality of life of people with HIV and their access to health services. This study aimed to assess HIV-related knowledge, attitudes and practices among healthcare workers (HCWs) in Oman. Methods: This cross-sectional study took place between July and November 2016. A questionnaire was distributed to 1,400 government HCWs to determine HIV-related knowledge, attitudes and practices. Results: A total of 1,281 HCWs participated (response rate = 92%). Routine tasks, such as dressing wounds, drawing blood and touching clothes, were a cause of concern for 24–52% of HCWs. Only 69% correctly answered questions regarding the transmission of HIV via eating/drinking and mosquito bites. Compared to other HCWs, doctors had significantly higher knowledge (mean = 0.46, 95% confidence interval [CI]: 0.19 to 0.73; P <0.001), attitude (mean = 0.77, 95% CI: 0.31 to 1.24; P = 0.001) and practice (mean = 2.07, 95% CI: 1.59 to 2.55; P <0.001) scores. Expatriates also scored significantly higher in knowledge (mean = 1.08, 95% CI: 0.93 to 1.23; P <0.001), attitude (mean = 1.23, 95% CI: 0.98 to 1.48; P <0.001) and practice (mean = 1.08, 95% CI: 0.82 to 1.34; P <0.001) compared to Omani nationals. Finally, those with >15 years’ work experience scored significantly higher on knowledge (mean = −0.60, 95% CI: −1.12 to −0.08; P = 0.025) and attitude (mean = −0.99, 95% CI: −1.87 to −0.10; P = 0.029) compared to those with less experience. Conclusion: The high rate of HIV-related stigma among HCWs in Oman should be rectified in order to achieve the 90-90-90 target set by the Joint United Nations Programme on HIV/AIDS.